Carotid artery disease: knowing the numbers. (2nd July 2022) - Heyes, Adam; Crichton, Alexander; Rajagopalan, Sriram
Abstract : Ischaemic stroke and transient ischaemic attack are of particular interest to the vascular surgeon as over one-third of all strokes are caused by thromboembolism from a stenotic carotid artery, making carotid artery stenosis the leading cause of stroke. If detected early, stenosis can be managed medically, surgically or endovascularly. However, treatment decisions depend on the timing of the transient ischaemic attack and the degree of stenosis, and must be balanced against procedural risk. This article discusses the evidence outlining the epidemiology, measurement and surgical management of carotid artery stenosis that inform national guidelines. Vascular and non-vascular trainees should understand these guidelines because of the potentially debilitating or fatal consequences of untreated carotid stenosis.